Penerapan Evaluasi Pembelajaran Berbasis Digital Untuk Menilai Perkembangan Kognitif Anak Usia Dini - Dwi Nomi Pura; Zona Junita Sari; Despi Despi; Novita Sari (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The development of digital technology has significantly influenced various aspects of life, including education. In the context of early childhood education, the use of digital technology can support a more effective and engaging learning evaluation process for children. Digital-based learning evaluation is an innovation in education that allows educators to conduct assessments in a more systematic, interactive, and efficient manner (Rahmawati & Handayani, 2023).Learning evaluation in early childhood education is essential to determine children's cognitive development, such as thinking skills, concept understanding, problem-solving abilities, and memory of learned information. Through appropriate evaluation, teachers can obtain information about children's cognitive development levels and design learning strategies that align with their developmental needs (Hidayat & Lestari, 2024). In this regard, the use of digital media such as learning applications, online assessment platforms, and other technological tools can assist teachers in assessing children's cognitive development more effectively and engagingly (Sari & Wibowo, 2023).This article aims to describe the implementation of digital-based learning evaluation in assessing early childhood cognitive development and to explain the benefits of using digital technology in the learning evaluation process. The research method used in this study is a literature review by examining various sources such as books and scientific journals relevant to the research topic (Nugraha & Damayanti, 2025). The findings indicate that the implementation of digital-based learning evaluation provides several benefits in assessing early childhood cognitive development. Digital evaluation improves the effectiveness of the assessment process, provides faster feedback, and helps teachers document children's learning progress more systematically (Putri & Kurniawan, 2024). Furthermore, the use of digital technology in learning evaluation can increase children's motivation and interest in learning because evaluation activities can be presented in more interactive and enjoyable forms (Marlina & Setiawan, 2023). Therefore, the implementation of digital-based learning evaluation can be an effective alternative to support the assessment of cognitive development in early childhood education.